Analisis Pengaruh Brand Image, Kualitas Produk, dan Harga Terhadap Keputusan Pembelian Printer Canon di Surabaya - Ayisyah Nirvananda Hidayat; Tanuwijaya, Haryanto; Suhandiah, Sri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research looks at Canon printer sales in Surabaya through the prism of price, product quality, and brand perception. The study used a quantitative methodology to gather primary data from 112 Canon printer users who were selected through purposive sampling. Using a five-point Likert scale, sixteen indicators were assessed and analyzed in SmartPLS using PLS SEM. “ Reliability, discriminant validity, and convergent validity tests confirmed that all constructs met the criteria (outer loading > 0.70; AVE > 0.50; CR > 0.70).  Product quality (β = 0.261; p = 0.007), brand image (β = 0.359; p = 0.003), and price (β = 0.293; p = 0.005)” all positively and significantly impact purchase decisions, with brand image accounting for 61.5 % of the variation (R² = 0.615).  All three predictors are categorized as moderate contributors (f² ≈ 0.10-0.17) according to the effect size study.  These results suggest that in order to increase sales in Surabaya's printer market, Canon needs to work on improving its brand image, adding more features to its products, and keeping pricing low.